Six hitherto unreported Basidiomycetic macrofungi from Kashmir Himalayas - SHAUKET AHMED PALA; ABDUL H. WANI; MOHMAD YAQUB BHAT (Smujo International, 2011)
Pala SA, Wani AH, Bhat MY. 2011. Six hitherto unreported Basidiomycetic macrofungi from Kashmir Himalayas. Nusantara Bioscience 3: 92-97. The Kashmir valley located in the north extreme of the India lies between 330 20’ and 340 54’ N latitude and 73 35’ E longitude. The forests constituting more than 20% of the geographical area harbors diverse macrofungal species due to their wide variability in climate altitude and nature of species constituting them. The mushroom flora of the Kashmir Valley has not been documented completely until now. In this backdrop, a systematic survey for exploration and inventorization of macrofungal species of Western Kashmir Himalaya was undertaken during the year 2009-2010. During the study six species viz. Agrocybe molesta, Coprinus plicatilis, Inonotus hispidus, Paxillus involutus, Psathyrella candolleana and Russula fragilis were identified first time from the Kashmir.